La grande lacune du Codex de Bèze - Amphoux, Christian-B. (Filología neotestamentaria, 2004)
One of the most important NT manuscripts, the codex Bezae, included between the Gospels and the Book of Acts several writings that are nowadays lost. The present article corrects the author’s former views, published in 1996, concerning the contents of this lacuna: the 66 missing pages may very well have included a seven letters corpus, in fact a forerunner of the Catholic Epistles corpus, including Hb but not yet Jd. The analysis of these letters allows us both to understand better the period of redaction of NT writings and to bring this enterprise in connection with the writing process of the Old Testament.